PENGARUH SELF-EFFICACY MENGAJAR,LITERASI DIGITAL, DAN PERSEPSI KESEJAHTERAAN GURU TERHADAP MINAT MENJADI GURU PADA MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN - Sri Wahyuningsih; Ahmad Saeroji (Jurnal Manajemen Pendidikan, 2026)
This study was conducted to analyze the influence of teaching self-efficacy, digital literacy, and teachers’ perceptions of well-being on the interest of Office Administration Education students in becoming teachers. The study employed a quantitative approach using a survey method. The sampling technique used was saturation sampling. The study population consisted of 122 students in the Office Administration Education program from the 2022 cohort. Data collection was conducted via a questionnaire using a 5-point Likert scale and analyzed using SPSS 22. The results of the study indicate that, individually, teaching self-efficacy and perceptions of teacher well-being have a positive and significant influence on students’ interest in becoming teachers. Digital literacy, however, does not have a significant influence. Simultaneously, these variables mutually influence students’ interest in becoming teachers. The novelty of this study lies in the fact that no previous research has addressed digital literacy within the Office Administration program, and teachers’ perceptions of well-being have not been extensively studied. Furthermore, no prior research has examined all three variables together.